1986
DOI: 10.1159/000249351
|View full text |Cite
|
Sign up to set email alerts
|

Keratoderma climactericum (Haxthausen’s Disease): Clinical Signs, Laboratory Findings and Etretinate Treatment in 10 Patients

Abstract: 10 cases of keratoderma climactericum are reported. This keratosis of the palms and soles appears late in women of menopausal age. The keratotic lesions first develop at the plantar pressure points, making walking troublesome. Involvement of the hands remains discrete. Examination for contact allergy, fungal tests, vitamin A serum levels, and sex hormones were negative or normal in all the 10 patients. Microscopy revealed a lichenified eczema with evidence of mechanical irritation. Etretinate (0.78 mg/kg/day) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 8 publications
0
17
0
2
Order By: Relevance
“…Lowdose maintenance therapy with etretinate at approximately 10-20 mg/day is needed for long-term treatment in order to prevent relapse [4,5], Recently, some new data demonstrated that keratoderma climactericum of Haxthausen's responded well to etretinate [6], In keratosis lichenoides chronica [7], Kyrlc's disease [8] and con fluent and reticulated papillomatosis [9], some rare hyper-and dyskcratotic diseases, etretinate has been reported to produce good results within 3-4 weeks. Concerning its mechanism of action, etretinate inhibits the migration of neutrophilic and eo sinophilic granulocytes by a direct effect on cell motility [10], probably by changing the cells' capability to respond to chemoattrac tants or by modulating components of the epidermis or basal membrane zone to act as chemoattractants.…”
Section: Etretinatementioning
confidence: 99%
“…Lowdose maintenance therapy with etretinate at approximately 10-20 mg/day is needed for long-term treatment in order to prevent relapse [4,5], Recently, some new data demonstrated that keratoderma climactericum of Haxthausen's responded well to etretinate [6], In keratosis lichenoides chronica [7], Kyrlc's disease [8] and con fluent and reticulated papillomatosis [9], some rare hyper-and dyskcratotic diseases, etretinate has been reported to produce good results within 3-4 weeks. Concerning its mechanism of action, etretinate inhibits the migration of neutrophilic and eo sinophilic granulocytes by a direct effect on cell motility [10], probably by changing the cells' capability to respond to chemoattrac tants or by modulating components of the epidermis or basal membrane zone to act as chemoattractants.…”
Section: Etretinatementioning
confidence: 99%
“…Thus, impaired permeability barrier recovery and weakened integrity of the SC could cause so‐called dry skin in postmenopause in combination with reduced hydration of the SC, although these were not analysed in women at menopause and postmenopause. The abnormalities of the SC, particularly impaired integrity, might be related to keratoderma climactericum, in which palmar and plantar keratosis appear on the sites experiencing mechanical pressure. This disease is found in not only postmenopausal women but also in young women who were castrated by surgery, and their symptom disappeared after HRT …”
Section: Discussionmentioning
confidence: 99%
“…Кератодермия климактерическая (болезнь Хакст-хаузена) -одна из самых распространенных форм приобретенной диффузной кератодермии, развива-ется у 10-15% женщин в климактерическом перио-де, чаще в местах давления и трения, обычно сочета-ется с метаболическим синдромом, гипертониче-ской болезнью, деформирующим артрозом [30]. Основным триггерным фактором в развитии этой кератодермии считается дефицит эстрогенов, про-гестерона, тестостерона, развивающийся в процессе возрастной инволюции репродуктивной системы.…”
Section: клиническая дерматология и венерология 2 2015unclassified
“…Жжение, зуд и боли при физической нагрузке связа-ны с наличием трещин. Заболевание имеет прогрес-сирующее течение, протекает волнообразно с пери-одами обострения, чаще в зимнее время [30]. Дости-жение полной ремиссии наблюдается редко.…”
Section: клиническая дерматология и венерология 2 2015unclassified